Synthesis, Characterization of Silver Nanoparticles Using Nigella sativa Seeds and Study Their Effects on the Serum Lipid Profile and DNA Damage on the Rats’ Blood Treated with Hydrogen Peroxide - Ali, Zainab Sattar; Khudair, Khalisa Khadim (The Iraqi Journal of Veterinary Medicine, 2019)
This study was aimed to produce silver nanoparticles using aqueous extract of Nigella sativa, also to investigate the effects of green synthesized Nigella sativa seeds silver nanoparticles on dyslipidemia and DNA fragmentation in hydrogen peroxide-exposed rats. The produced Nigella sativa seeds silver nanoparticles were characterized through Ultraviolet-Visible spectroscopy, Fourier-transform infrared spectroscopy, X-ray powder diffraction (XRD) style, and Scanning Electron Microscope was used to investigate the morphology and size of synthesized Nigella sativa seeds silver nanoparticles. Forty adults male rats were randomly and equally divided into five groups and daily had been remedying for two months as followings: G1 group (Control), G2 group, rats in this group were received tap water containing 1% H2O2, animals in G3 and G4 groups were injected IP Nigella sativa seeds silver nanoparticles 25 and 50 mg/kg B.W., respectively, and received ordinary tap water containing 1% H2O2 , and G5 group, animals in this group were injected IP Nigella sativa seeds extract 50 mg/kg B.W. and received ordinary tap water containing 1% H2O2. Blood samples collected after one and two months of the experiment from each animal for DNA fragmentation measurements and serum estimated lipid profile.The results receded a case of dyslipidemia, as well significant elevation in DNA damage in G4 and G2 groups The results also confirmed the hypolipidemic and cytoprotective effect of Nigella sativa seeds extract (G5 group) and silver nanoparticles as25mg/kg B.W (group G3) clarified by correction of dyslipidemia, alongside significant alleviation in DNA damage. In conclusion, the results in the current study effectsof Nigella sativa seeds silver nanoparticles at high dose and documents the ameliorative effect of Nigella sativaseeds extract and Nigella sativa seeds silver nanoparticles on lipid profile and DNA damage.